Cost analysis and outcomes of a second‐look tympanoplasty‐mastoidectomy strategy for cholesteatoma. (1st March 2016) - Crowson, Matthew G.; Ramprasad, Vaibhav H.; Chapurin, Nikita; Cunningham, Calhoun D.; Kaylie, David M.
Abstract : Objectives/Hypothesis: To analyze cost and compare cholesteatoma recidivism and hearing outcomes with single‐stage and second‐look operative strategies. Study Design: Retrospective review and cost analysis. Methods: Adult and pediatric patients who underwent a tympanoplasty with mastoidectomy for cholesteatoma with a single‐stage or second‐look operative strategy were identified. Variables included procedure approach, residual or recurrent cholesteatoma, ossicular chain reconstruction frequency, and operative complications. Audiologic outcomes included pre‐/postoperative air bone gap (ABG) and word recognition score (WRS). Cost analysis included charges for consultation and follow‐up visits, surgical procedures, computed tomography temporal bone scans, and audiology visits. Results: One hundred and six patients had a tympanoplasty with mastoidectomy for cholesteatoma, with 80 canal wall‐up procedures (CWU) as initial approach. Of these, 46 (57.5%) CWU patients had a planned second look. Two (4.3%) CWU patients had recurrent cholesteatoma and 20 (43.4%) had residual identified at second look. Four (11.7%) single‐stage CWU strategy patients developed recurrent cholesteatoma. There was no significant difference in pre‐/postoperative ABG and WRS between second look and single stage ( P > 0.05). Compared to second‐look patients, single‐stage patients had significantly fewer postoperative visits (6.32 vs. 10.4; P = 0.007), and significantly lower overall charges for care ($23, 529. vs. $41.411; P < 0.0001). Conclusion: The goal of cholesteatoma surgery is to produce a safe ear, and a second‐look strategy after CWU has historically been used to evaluate for recurrent or residual disease. The cholesteatoma recurrence rate at a second look after a CWU tympanoplasty‐mastoidectomy is low. Costs of operative procedures are a significant proportion of healthcare resource expenditures. Considering the low rate of cholesteatoma recurrence and relatively high cost of care, implementation of a second‐look strategy should be individually tailored and not universally performed. Level of Evidence: 4. Laryngoscope, 126:2574–2579, 2016